This is a classic translators on making writers global - Galasso, Regina (New York Bloomsbury Academic, 2023)
Translators reflect on what it means to translate literary classics and canonical texts from a variety of languages into English"--Provided by publisher.
Introduction : literary classics through translation / Regina Galasso. Prologue: the translator's agency and the literary classic abroad: Emily Dickinson's Voyage to Brazilliput / Adalberto Muller -- 1. Chinese classics: the commentarial tradition / Sabina Knight with Kidder Smith -- 2. Happy hour homer: on translating and performing the iliad live in a bar / Lynn Kozak -- 3. Today in the temple of language: translating Dante / Mary Jo Bang -- 4. True confession of a literary translator / Arvind Krishna Mehrotra -- 5. What is a classic? The case of Esperanto / Humphrey Tonkin -- 6. The Russian canon in retranslation / Marian Schwarts -- 7. Translating Yiddish classics: redefining tradition in modern Yiddish literature through the prism of Kadya Molodowsky Chantal Ringuet -- 8. Victor Catalas film (3000 meters): translating a Catalan classic / Peter Bush -- 9. Translation as storytelling / Susan Bernofsky -- 10. In terror and pandemic: translating Garcia Lorcas in New York / Mark Statman -- 11. Stopping at the surface: translating Clarice Lispector's The Besieged City and a Breath of Life / Johnny Lorenz -- 12. Tanizaki's the key in translation: will you still need me, will you still read me, when I'm over sixty-four? / Anna Zielinska-Elliott -- 13. An essay on Nichita Stanescu: the classic and the personal in translation / Sean Cotter -- 14. From Arabic to English, what is a classic? / Michelle Hartman -- 15. Translating a classic into the future: Tomas Jonsson-bestseller / Lytton Smith -- 16. Love, anger, madness making a classic: amplifying Marie Vieux-Chauvet's Haitian trilogy / Carolyn Shread -- 17. What besides words? Translating bilge karasu's A Long Day's Evening / Aron Aji -- 18. Nonsense in a given direction: translating the timelessness of Marguerite Duras / Emma Ramadan -- 19. "Sentence" as lifeline: translating David Albahari's novels / Ellen Elias-Bursac -- Epilogue: matching socks in the dark; or how to translate from languages you don't know / Ilan Stavans -- A translation experiment: kleptomaniac classic: Ramona Esther Allen and Sean Cotter.
Includes bibliographical references and index.
Keywords: Canon (Literature) -- Translations into English -- History and criticism; Translating and interpreting